Outcome of 1000 Patients With Gastrointestinal Stromal Tumor (GIST) Treated by Surgery in the Pre- and Post-imatinib Eras. Issue 1 (January 2021) - Cavnar, Michael J.; Seier, Kenneth; Curtin, Christina; Balachandran, Vinod P.; Coit, Daniel G.; Yoon, Sam S.; Crago, Aimee M.; Strong, Vivian E.; Tap, William D.; Gönen, Mithat; Antonescu, Cristina R.; Brennan, Murray F.; et al.
Abstract : Objective: To characterize the results of surgery for gastrointestinal stromal tumor (GIST) in the pre and post-imatinib eras at a single institution and to identify current prognostic clinicopathologic factors. Background: Imatinib has radically changed the management of GIST, yet the magnitude of impact on outcome across the spectrum of GIST presentation and relevance of historical prognostic factors are not well defined. Methods: We retrospectively analyzed 1000 patients who underwent surgery for GIST at our institution from 1982 to 2016. Patients were stratified by presentation status as primary tumor only (PRIM), primary with synchronous metastasis (PRIM + MET), or metachronous recurrence/metastases (MET), and also imatinib era (before and after it became available). Cox proportional-hazard models and Kaplan-Meier methods were used to model and estimate overall survival (OS) and recurrence-free survival (RFS). Results: OS was longer in the imatinib era compared with the pre-imatinib era in each presentation group, including in Miettinen high-risk primary tumors. Among PRIM patients from the pre-imatinib era, tumor site, size, and mitotic rate were independently associated with OS and RFS on multivariate analysis. PRIM patients in the imatinib era who received imatinib (neoadjuvant and/or adjuvant) had higher risk tumors, but after adjusting for treatment, only size >10 cm remained independently prognostic of RFS [hazard ratio (HR) 3.85, 95% confidence interval (CI) 2.00–7.40, P < 0.0001) and OS (HR 3.37, 95% CI 1.60–7.13, P = 0.001)]. Conclusions: Patients treated in the imatinib era had prolonged OS across all presentations. In the imatinib era, among site, size, and mitotic rate, high-risk features were associated with treatment with the drug, but only size >10 cm correlated with outcome. Imatinib should still be prescribed for patients with high-risk features. Abstract : Supplemental Digital Content is available in the text